One-pot Synthesis of MoS2(1-x)Se2x on N-doped Reduced Graphene Oxide: Tailoring Chemical and Structural Properties for Photoenhanced Hydrogen Evolution Reaction - Mosconi, Dario; Kosmala, Tomasz; Lunardon, Marco; Neyman, Alevtina; Bar Sadan, Maya; Agnoli, Stefano; Granozzi, Gaetano (Nanoscale Advances, 2020)
Molybdenum sulfoselenides are investigated as photoelectrocatalysts for the hydrogen evolution reaction. Crystallinity and selenium-to-sulphur ratio are key to control activity.